Microstructure engineering of a nickel base superalloy manufactured by powder bed fusion - Ng, Darren Teng How (Nanyang Technological University, 2022)
Nickel-based superalloy Inconel 725 (IN 725) has been known for its excellent resistance to corrosion and superior mechanical properties even at elevated temperatures. The material has been widely used in oil and gas, marine, and aerospace industries. However, when the alloy is subjected to hydrogen-present environments, its mechanical properties tend to degrade in a phenomenon called hydrogen embrittlement (HE). Through microstructure engineering, it may be possible to enhance IN725’s resistance to HE. Σ3 coherent twin boundaries (CTB) are known to be susceptible to crack initiation but are resistant to crack propagation in the presence of hydrogen. In this project, near dense Σ3-rich and Σ3-free microstructures were manufactured by varying the volumetric energy density during laser powder bed fusion. Σ3-rich microstructures (with 48% CTB fraction and 82.7% recrystallized grain fraction) and Σ3-free microstructures (with 0.127% CTB fraction and 2.1% recrystallized grain fraction) were successfully fabricated. Tensile tests of the homogenous samples showed higher ductility in samples with Σ3-rich microstructure while samples with Σ3-free microstructures yielded higher strength. Alternating Σ3-rich and Σ3-free microstructured heterogeneous lamella samples were printed with increasing domain thickness. Electron Backscatter Diffraction scans showed domains printed with 3 or less layers of 35μm theoretical layer thickness were indistinguishable from each other. Average actual thicknesses of the two microstructures per theoretical 35μm layer were also calculated. Σ3-rich microstuructured domains tend to be thicker while Σ3-free microstuructured domains are thinner when compared to the theoretical thickness. This suggests that the melt pool geometries for both microstructures are different. The data obtained from this project could pave the way for future works on heterogeneous lamella microstructured superalloy components for applications in extreme environments.